PS2:24 Plasmatic and urinary endothelial microparticles are increased in patients with lupus nephritis. (21st March 2018) - Miranda, F; Barbati, C; Truglia, S; Spinelli, FR; Ceccarelli, F; Alessandri, C; Valesini, G; Conti, F
Abstract : Systemic lupus erythematosus(SLE) is a chronic autoimmune disease, characterised by alterations in both the innate and adaptive immune system ultimately leading to the loss of immunologic tolerance and occurrence of autoantibodies against nuclear material. Lupus nephritis is one of the most severe features of SLE determining an increase in morbidity e mortality rates.Renal biopsy still represent a fundamental diagnostic and prognostic tool for LN.Therefore, non-invasive surrogate biomarkers of active LN are urgently needed.Circulating, heterogeneous subcellular microparticles(MPs) are released from cells and platelets constitutively and upon cellular activation or apoptosis.Such MPs may reflect the state of their parental cells and tissues, and could serve as markers of pathology. Particularly in SLE, MPs are potential biomarkers and triggers of autoimmunity.Recent studies have demonstrated increased of plasmatic EMPs in patients with SLE active disease and their reduction after treatment. The aim of this study was to investigate levels of EMPs in a cohort of SLE patients with and without renal involvement compared to healthy controls. MPs were isolated from plasma and urine and characterised by flow cytometry using AnnessinV (a probe that binds to the exposed phosphatidilserine – PS)and antibodies against surface markers endothelial cells(CD31 +CD41-). Sixty SLE patients and 29HC were studied. Twenty-eight patients had renal involvement. The total number of plasmatic MPs was lower in SLE patients than HC(p=0.001). In contrast there was no significant difference EMPs between the two groups. When the patients were divided according to renal involvement, the patients with active-LN(A-LN) showed lower plasmatic EMPs in comparison to inactive LN(I-LN) (p=0.01), while the patients with I-LN had higher EMPs than HC(p=0.002).There was no significant difference of total urinaryMPs between SLE patients and HC. UrinaryEMPs were higher in SLE and in LN patients than HC. The results of the present study show increased EMPs in patients with LN in remission. Circulating-EMPs have been considered as a potential biomarker of endothelial activation and damage in several autoimmune disorders, and higher EMP have been detected in patients with vasculitis and associated with disease activation. According to our results, plasmatic EMPs are higher in inactive-LN patients than in HC. These results may suggest a potential role of EMP as a biomarker of LN.